(untitled) (National Administration Journal, 2025)
This article is based on research on the state of the art of the Marketing program at the School of Administrative Sciences of UNED Costa Rica during the 2024–2025 period, with the objective of updating the curriculum of this program. A qualitative approach with quantitative features was applied, combining documentary review of national and international curricula, interviews with faculty, graduates, students, and professionals in the field. The findings revealed the importance of digital marketing, artificial intelligence, neuromarketing, and sustainability. It was concluded that the curriculum requires strengthening some of these competencies to respond to the demands of the labor market. Keywords: Distance education, university curriculum, marketing, artificial intelligence, sustainability